Near-Native Sociolinguistic Competence in French: Evidence from Variable Future-Time Expression - Gudmestad, Aarnes; Edmonds, Amanda; Donaldson, Bryan; Carmichael, Katie (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
This study aims to advance the understanding of sociolinguistic competence among near-native speakers and to further knowledge about the acquisition of variable structures. We conduct a quantitative analysis of variable future-time expression in informal conversations between near-native and native speakers of French. In addition to examining linguistic constraints that have been investigated in previous research, we build on prior work by introducing a new factor that enables us to consider the role that formality of the variants plays in the use of variable future-time expression. We conclude by comparing these new findings to those for the same dataset and other variable structures (namely, negation and interrogatives, Donaldson, 2016, 2017) and by advocating for more research that consists of multiple, complementary analyses of the same dataset.